Tundish coating material and preparation method thereof

By using tundra coatings composed of magnesium sand, calcium-based bentonite, silica fume, paper fiber, water reducing agent and ground-polymer cement, the problem of traditional coatings being prone to cracks and peeling at high temperatures is solved, and higher density and structural strength are achieved, which extends service life and improves the quality of the billet.

CN119899038APending Publication Date: 2025-04-29SHANXI TONGBANG TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510117967.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Traditional tundra coatings are prone to cracks, peeling and blocking at high temperatures, which affects their service life and billet quality.

Method used

The tundra coating consisting of magnesium sand, calcium-based bentonite, silica fume, paper fiber, water reducing agent and binding agent (such as polypeptide cement) is used to form a dense magnesium silicate sintered layer through the reaction of magnesium sand and silica fume, which improves the density and structural strength of the coating, and improves its rheological properties and high temperature stability through water reducing agent and bentonite.

Benefits of technology

It significantly improves the density and structural strength of the tundra coating, reduces the occurrence of cracks and peeling, extends the service life of the coating, and improves the quality of the billet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005258260740000051
    Figure BDA0005258260740000051
  • Figure BDA0005258260740000061
    Figure BDA0005258260740000061
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, and particularly discloses a tundish coating material and a preparation method thereof. The tundish coating material is prepared from the following raw materials in parts by weight: 80 to 110 parts of magnesia, 0.5 to 1 part of calcium bentonite, 2 to 3 parts of silica fume, 1 to 2 parts of paper fiber, 0.1 to 0.2 part of a water reducing agent and 2 to 4 parts of an accelerating binding agent, the magnesite is a mixture of 92 magnesite and 95 magnesite, and the promoting binding agent comprises geopolymer cement; magnesium oxide in a mixture of 92 magnesia and 95 magnesia reacts with silicon dioxide in silica fume, so that the coating material has relatively good structural strength and compactness, the water reducing agent can be used for reducing the water consumption for mixing the coating material, and the calcium bentonite can be used for improving the plasticity and cohesiveness of the coating material; the geopolymer cement is added instead of lime in a traditional formula, so that the bonding strength of the coating material is improved, and the phenomena of cracking, peeling, chipping and even bag collapse of the coating material during baking are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of refractory materials, and in particular to a tundish coating material and a preparation method thereof. Background Art

[0002] The tundish is an important equipment in the steel production process, used to contain molten steel and maintain its fluidity during the continuous casting process. The traditional lining materials of the tundish are mainly refractory bricks and amorphous refractory materials, which have good corrosion resistance and thermal stability at high temperatures and can effectively protect the tundish from direct impact and erosion of the molten steel.

[0003] The use of tundish coating can not only improve the quality of steel billets and the service life of the tundish working lining, but also reduce the consumption of tundish refractory materials. At present, the tundish coating is mainly composed of a mixture of fine refractory aggregates, lime, powder, and binder. During construction, it is necessary to add an appropriate amount of water to the coating and stir it into mud, then apply it to the surface of the tundish, and then cure and harden it. During the curing time, the lime will expand, and the coating is prone to cracking, falling off, and peeling. Summary of the invention

[0004] In order to improve the problems of cracking, peeling and so on of the existing tundish coating, the present application provides a tundish coating and a preparation method thereof.

[0005] In the first aspect, the present application provides a tundish coating material, which adopts the following technical solution: A tundish coating material comprises the following raw materials in parts by weight: 80-110 parts of magnesia, 0.5-1 parts of calcium-based bentonite, 2-3 parts of silica fume, 1-2 parts of paper fiber, 0.1-0.2 parts of water reducing agent, and 2-4 parts of promoting binding agent; the magnesia is a mixture of 92 magnesia and 95 magnesia, and the promoting binding agent comprises geopolymer cement.

[0006] By adopting the above technical scheme, the magnesium content in 92 magnesia sand is 92%, and the magnesium content in 95 magnesia sand is 95%. The magnesium oxide in the mixture of 92 magnesia sand and 95 magnesia sand reacts with the silicon dioxide in the silica ash to form a dense magnesium silicate sintering layer, thereby improving the density and structural strength of the coating, and reducing cracks and peeling. The water reducer can reduce the amount of water used in mixing the coating, improve the rheological properties of the coating, and reduce the shrinkage of the coating during the drying process, thereby reducing the formation of cracks and improving the anti-stripping performance of the coating. Calcium-based bentonite can improve the plasticity and adhesion of the coating. At high temperatures, the water in the bentonite evaporates to form a microporous structure. These microporous structures can promote the discharge of water during the curing process, increase the curing and hardening speed of the coating, and reduce the phenomenon of cracking, peeling, falling off, and collapsing caused by the concentrated discharge of water from the coating during baking. Paper fibers can form a network structure in the coating, enhance the toughness of the coating, prevent cracking and peeling during drying and high-temperature use, and improve the coating's crack resistance and peeling resistance. Geopolymer cement is a polymer cement that can form a dense sintered layer at high temperatures, enhance the structural strength of the coating, and reduce the risk of cracking and peeling. Eliminate the addition of lime in the traditional formula to reduce the cracking, falling, and peeling of the coating caused by the expansion of lime reaction.

[0007] Preferably, the mass ratio of 92 magnesia sand to 95 magnesia sand is 70:(20-30).

[0008] Preferably, the particle size of the 92 magnesia sand is 0.5-3 mm, and the particle size of the 95 magnesia sand is 180-250 mesh.

[0009] Preferably, the promoting binder comprises geopolymer cement and magnesia cement, and the magnesia cement is at least one of magnesium oxychloride cement and magnesium oxysulfate cement.

[0010] By adopting the above technical scheme, magnesium oxychloride cement and magnesium oxysulfate cement can make magnesia water generate magnesium hydroxide. Magnesium hydroxide has a gelling effect, thereby enhancing the bonding force of the coating, thereby improving the bonding strength and density of the coating and reducing the occurrence of cracks.

[0011] Preferably, the geopolymer cement comprises the following raw materials in parts by weight: 40-60 parts of metakaolin, 1-5 parts of sodium metasilicate, and 1-3 parts of redispersible latex powder.

[0012] By adopting the above technical solution, metakaolin is obtained by calcining traditional kaolin at a high temperature of 800-900℃. Metakaolin can form a high temperature resistant polymer after being stimulated by sodium metasilicate, which can make the structure of the coating more compact. At the same time, the polymer has a certain gelling property, which further improves the bonding strength of the coating. After the redispersible latex powder is dispersed in the coating, it can form a network structure, enhance the toughness of the coating, and reduce the occurrence of cracks and peeling under drying and high temperature.

[0013] Preferably, the method for preparing the redispersible latex powder comprises the following specific steps: The polyvinyl alcohol and vinyl acetate-ethylene copolymer emulsion are mixed and stirred evenly to form a dispersed mixed liquid, the dispersed mixed liquid is heated to 60-65° C. and spray-dried to obtain spray-dried particles, the spray-dried particles are mixed with a dispersing aid component, and after cooling and dehumidification, a redispersible latex powder is obtained.

[0014] By adopting the above technical solution, using vinyl acetate-ethylene copolymer emulsion as the main material, polyvinyl alcohol plays the role of protective colloid, and the prepared redispersible latex powder is added to the coating material. It can be quickly dispersed and form an emulsion in the coating material system by utilizing its own good redispersibility, occupying the cavity produced by the hardening of magnesium sand in the coating material, reducing the moisture content in the cavity, and further reducing the phenomenon of dehydration and cracking of the coating material after hardening. As the geopolymer cement gradually dries in the coating material, the redispersible latex powder can be dehydrated again in the coating material system to form a polymer film, and then continuously distributed around the cavity produced by the hardening of the coating material. The polymer film can absorb external stress in time and improve the bonding strength and strength of the coating material.

[0015] Preferably, the mass ratio of the spray-dried particles to the dispersing aid is 1:(0.1-0.3), the dispersing aid is ultrafine calcium carbonate, and the particle size of the ultrafine calcium carbonate is 20-80 nm.

[0016] In a second aspect, the present application provides a method for preparing a tundish coating material, using the following technical solution: A method for preparing a tundish coating material comprises the following specific steps: Mix 92% magnesia sand and 95% magnesia sand, add calcium-based bentonite, silica fume, paper fiber, promoting bonding agent and water reducing agent, mix well, and obtain the tundish coating material.

[0017] By adopting the above technical solution, under the synergistic effect of various components, the density and structural strength of the coating can be improved, the shrinkage of the coating during the drying process can be reduced, and cracks and peeling can be reduced.

[0018] Preferably, the method comprises the following specific steps: Mix kaolin, sodium metasilicate and redispersible latex powder, stir evenly to obtain geopolymer cement, and then mix with magnesium chloride cement and magnesium sulfate cement to form a promoting binder; mix 92 magnesia sand and 95 magnesia sand, then add calcium-based bentonite, silica fume, paper fiber, water reducer and promoting binder, stir evenly to obtain the tundish coating.

[0019] In summary, this application has the following beneficial effects: 1. Since the magnesium oxide in the mixture of 92 magnesia sand and 95 magnesia sand reacts with the silicon dioxide in the silica ash in this application to form a dense magnesium silicate sintered layer, the density and structural strength of the coating are improved. The use of a water reducer can reduce the amount of water used in the coating, reduce the shrinkage of the coating during the drying process, and thus reduce the formation of cracks. At the same time, the use of calcium-based bentonite can improve the plasticity and adhesion of the coating, and reduce the cracking and peeling caused by the discharge of water in the coating under high-temperature baking.

[0020] 2. In this application, metakaolin, sodium metasilicate and redispersible latex powder are used to form geopolymer cement, which can enhance the bonding strength of the coating system, enhance the toughness of the coating, and reduce the occurrence of cracks and peeling under drying and high temperature. Vinyl acetate-ethylene copolymer emulsion is used as the main material, polyvinyl alcohol can protect the colloid, and the generated redispersible latex powder can be quickly dispersed in the coating to form a polymer film, reducing the cracking phenomenon caused by dehydration when the coating is drying. DETAILED DESCRIPTION

[0021] The present application is further described in detail below with reference to the embodiments.

[0022] All raw materials in the examples are commercially available. Example

[0023] Example 1 The present embodiment provides a tundish coating, comprising the following raw materials in parts by weight: 95 kg of magnesia, 0.8 kg of calcium-based bentonite, 2.5 kg of silica fume, 1.5 kg of paper fiber, 0.15 kg of water reducer, and 3 kg of promoting binder; wherein the magnesia is a mixture of 92 magnesia and 95 magnesia, the mass ratio of 92 magnesia to 95 magnesia is 70:25, the average particle size of 92 magnesia is 2 mm, the average particle size of 95 magnesia is 210 mesh, the water reducer is BASF polycarboxylic acid high-performance water reducer F10, and the promoting binder is geopolymer cement purchased from Huaqiansu Geopolymer No. 1.

[0024] The method for preparing the tundish coating material comprises the following specific steps: Mix 92% magnesia sand and 95% magnesia sand, add calcium-based bentonite, silica fume, paper fiber, promoting bonding agent and water reducing agent, mix well, and obtain the tundish coating material.

[0025] Example 2 The difference between Example 2 and Example 1 is that the amount of magnesia used in the raw materials of the ladle coating is 80 kg, the amount of calcium-based bentonite used is 1 kg, the amount of silica ash used is 2 kg, the amount of paper fiber used is 1 kg, the amount of water reducer used is 0.1 kg, and the amount of promoting bonding agent used is 2 kg.

[0026] Example 3 The difference between Example 3 and Example 1 is that the amount of magnesia used in the raw materials of the ladle coating is 110 kg, the amount of calcium-based bentonite used is 0.5 kg, the amount of silica ash used is 3 kg, the amount of paper fiber used is 2 kg, the amount of water reducer used is 0.2 kg, and the amount of promoting bonding agent used is 4 kg.

[0027] Example 4 The difference between Example 4 and Example 1 is that the promoting binder in the raw material of the ladle coating is a mixture of geopolymer cement and magnesia cement, the mass ratio of geopolymer cement to magnesia cement is 1:1, and the magnesia cement is magnesium oxychloride cement.

[0028] The method for preparing the tundish coating material comprises the following specific steps: Mix 92% magnesia sand and 95% magnesia sand, add calcium-based bentonite, promoting binder, silica fume, paper fiber and water reducing agent, mix well and obtain the tundish coating material.

[0029] Example 5 The difference between Example 5 and Example 4 is that the promoting binder in the raw material of the ladle coating is a mixture of geopolymer cement and magnesia cement, and the mass ratio of geopolymer cement and magnesia cement is 1:1, wherein the magnesia cement is a mixture of magnesium oxychloride cement and magnesium oxysulfate cement, and the mass ratio of magnesium oxychloride cement and magnesium oxysulfate cement is 1:1.

[0030] Example 6 The difference between Example 6 and Example 5 is that the geopolymer cement in the raw material of the promoting binder includes the following raw materials in parts by weight: 50 kg of metakaolin and 3 kg of sodium metasilicate.

[0031] The method for preparing the tundish coating material comprises the following specific steps: Mix kaolin and sodium metasilicate, stir evenly to obtain geopolymer cement, and then mix with magnesium chloride cement and magnesium sulfate cement to form a promoting binder; mix 92 magnesia sand and 95 magnesia sand, then add calcium-based bentonite, silica fume, paper fiber, water reducer, and promoting binder, stir evenly to obtain the tundish coating.

[0032] Example 7 The difference between Example 7 and Example 6 is that the geopolymer cement raw material also includes 2 kg of redispersible latex powder.

[0033] The method for preparing the tundish coating material comprises the following specific steps: S1: Mix polyvinyl alcohol with vinyl acetate-ethylene copolymer emulsion, the molecular weight of polyvinyl alcohol is 250,000, the mass ratio of polyvinyl alcohol to vinyl acetate-ethylene copolymer emulsion is 0.2:1, stir evenly to form a dispersed mixed liquid, heat the dispersed mixed liquid to 63°C, and then spray dry to obtain spray-dried particles, mix the spray-dried particles with a dispersing aid component, the mass ratio of the spray-dried particles to the dispersing aid is 1:0.2, the dispersing aid is ultrafine calcium carbonate, and the average particle size of the ultrafine calcium carbonate is 20-80nm. After cooling and dehumidification, redispersible latex powder is obtained.

[0034] S2: Mix kaolin, sodium metasilicate and redispersible latex powder, stir evenly to obtain geopolymer cement, form a promoting binder, mix 92 magnesia sand and 95 magnesia sand, add calcium-based bentonite, silica fume, paper fiber, water reducing agent and promoting binder, stir evenly to obtain the tundish coating material.

[0035] Example 8 The difference between Example 8 and Example 7 is that the amount of kaolin used in the geopolymer cement raw material is 40 kg, the amount of sodium metasilicate used is 1 kg, and the amount of redispersible latex powder used is 3 kg.

[0036] Example 9 The difference between Example 9 and Example 7 is that the amount of kaolin used in the geopolymer cement raw material is 60 kg, the amount of sodium metasilicate used is 5 kg, and the amount of redispersible latex powder used is 1 kg.

[0037] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that an equal amount of slaked lime is used in the raw material of the tundish coating instead of the promoting bonding agent.

[0038] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no bonding promoter is used in the raw material of the tundish coating.

[0039] Performance testing According to the ladle coating provided in Examples 1-9 and Comparative Examples 1-2 of the present application, 15% of water was added to the total mass and stirred evenly, and then the following performance tests were performed after molding, curing and roasting. The specific test results are shown in Table 1.

[0040] Detection Methods After adding 15% of the total mass of water to the tundish coating material prepared in this application and stirring evenly, smearing is performed to form a 70mm tundish coating layer, and then dried for 1 hour, covered with a 300°C red cover from a hot pack and cured for 1 hour. After the curing is completed, it is first baked at a low heat of 300°C for 60 minutes, then baked at a medium heat of 600°C for 30 minutes, and finally baked at a high heat of 800°C for 60 minutes. The tundish coating layer prepared in Examples 1-9 of this application was cast for 9 furnaces without any cracking or peeling. When the tundish coating layer prepared in Comparative Example 1-2 was cast for 6 furnaces, cracking and peeling occurred.

[0041] With reference to the standard of YB / T4121-2018 "Alkaline Coating for Tundish", the tundish coating prepared in this application was tested for volume density (110℃×24h, after drying), normal temperature compressive strength (110℃×24h), high temperature compressive strength (1500℃×3h), and heating permanent linear change (1500℃×24h).

[0042] Table 1: Performance test results data table It can be seen from the performance test results that the tundish coating prepared in this application has good density and strength. By comparing Examples 4-9 with Example 1, it can be seen that Examples 4-9 use a composite of geopolymer cement and magnesium oxychloride cement and magnesium oxysulfate cement to prepare a tundish coating with higher volume density and strength, and can still maintain good compressive strength at high temperatures. It further illustrates that geopolymer cement and magnesium oxychloride cement and magnesium oxysulfate cement can have a good reinforcement effect in the coating system. At the same time, the permanent linear change of the tundish coating is low at high temperatures, and it has good dimensional stability.

[0043] In Example 6 and Example 7, the geopolymer cement raw material prepared in Example 7 also includes dispersible latex powder. From the performance test results, it can be seen that the prepared ladle coating has higher strength and maintains good compressive strength at high temperature.

[0044] By comparing Comparative Examples 1-2 with Example 1, it can be seen that conventional slaked lime is used in Comparative Example 1, and no promoting binder is used in Comparative Example 2. From the performance test results, it can be seen that the strength and high temperature resistance of the prepared tundish coating material are greatly reduced, and the coating material surface has cracked during the high temperature baking process. This further illustrates that the present application uses geopolymer cement to replace conventional slaked lime, thereby reducing the slaked lime expansion reaction phenomenon, and synergizes with other components to promote the coating material to have higher strength and density.

[0045] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A tundish coating material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-110 parts of magnesia, 0.5-1 parts of calcium-based bentonite, 2-3 parts of silica fume, 1-2 parts of paper fiber, 0.1-0.2 parts of water reducing agent, and 2-4 parts of promoting binder; the magnesia is a mixture of 92 magnesia and 95 magnesia, and the promoting binder comprises geopolymer cement.

2. The tundish coating material according to claim 1, characterized in that: The mass ratio of the 92 magnesia sand to the 95 magnesia sand is 70:(20-30).

3. The tundish coating material according to claim 2, characterized in that: The particle size of the 92 magnesia sand is 0.5-3 mm, and the particle size of the 95 magnesia sand is 180-250 mesh.

4. The tundish coating material according to claim 1, characterized in that: The promoting binder comprises geopolymer cement and magnesia cement, and the magnesia cement is at least one of magnesium oxychloride cement and magnesium oxysulfate cement.

5. The tundish coating material according to claim 4, characterized in that: The geopolymer cement comprises the following raw materials in parts by weight: 40-60 parts of metakaolin, 1-5 parts of sodium metasilicate, and 1-3 parts of redispersible latex powder.

6. The tundish coating material according to claim 1, characterized in that: The method for preparing the redispersible latex powder comprises the following specific steps: The polyvinyl alcohol and vinyl acetate-ethylene copolymer emulsion are mixed and stirred evenly to form a dispersed mixed liquid, the dispersed mixed liquid is heated to 60-65° C. and spray-dried to obtain spray-dried particles, the spray-dried particles are mixed with a dispersing aid component, and after cooling and dehumidification, a redispersible latex powder is obtained.

7. The tundish coating material according to claim 6, characterized in that: The mass ratio of the spray-dried particles to the dispersing aid is 1:(0.1-0.3), the dispersing aid is ultrafine calcium carbonate, and the particle size of the ultrafine calcium carbonate is 20-80 nm.

8. A method for preparing a tundish coating material according to any one of claims 1 to 7, characterized in that: The specific steps include: Mix 92% magnesia sand and 95% magnesia sand, add calcium-based bentonite, silica fume, paper fiber, promoting bonding agent and water reducing agent, mix well, and obtain the tundish coating material.

9. The method for preparing a tundish coating material according to claim 8, characterized in that: The specific steps include: Mix kaolin, sodium metasilicate and redispersible latex powder, stir evenly to obtain geopolymer cement, and then mix with magnesium chloride cement and magnesium sulfate cement to form a promoting binder; mix 92 magnesia sand and 95 magnesia sand, then add calcium-based bentonite, silica fume, paper fiber, water reducer and promoting binder, stir evenly to obtain the tundish coating.